Replacement after standard versus prolonged use of administration sets for peripheral arterial catheter in an Australian intensive care unit: a feasibility randomised controlled trial - Daud, Azlina; Rickard, Claire; Cooke, Marie (Wichtig, 2014)
Introduction The prevalence of administration sets (AS) used for peripheral arterial catheter (PAC) of critically ill patients is not known, however, approximately six million PACs were placed yearly in the USA (Gowardman et al., 2010) which can estimate the use of AS for PAC to be at least the same number. Most recent research has investigated the prolonged use of AS associated with the incidence of CVC related BSIs with no recent studies on replacement of AS for PAC. Purpose To rigorously test the efficacy or equivalence of AS replacement for PAC at 4 days versus 7 days. Method The 13 months recruitment of patients was undertaken at The Prince Charles Hospital, Queensland. Recruitment was from July 2011 until July 2012. The researcher screened patients admitted to the ICU in relation to the inclusion criteria. Patients were randomised into two treatment groups; the control group had the PAC-AS replaced every four days and the experimental group had the PAC-AS replaced every seventh days. The study was approved by the Human Research Ethics Committees of the University and the Queensland Health multi-centre committee protocol member. Results 100 patients were randomised, 50 in the 4-day group and 50 in the 7-day group. Of the 50 patients in each group, 90% in the 4-day group and 60% in the 7-day group had the AS changed for the first time. There was zero percentage of CRBSI of the AS replacement for PAC at 4 days and 7 days. Discussion Information derived from this study provides clinicians the need for high quality evidence on the impact of extended, AS use for PAC beyond 4 days in the form of RCT is required. Conclusion There is limited evidence to suggest changing AS at 96 hours or more effects the risk of CRBSI among critically ill patients, indicating that large randomised trials of high quality are needed.